2021
DOI: 10.26803/ijlter.20.9.7
|View full text |Cite
|
Sign up to set email alerts
|

Using Pixton for Teaching EFL Writing in Higher Education during the Covid-19 Pandemic

Abstract: The study examined the use of Pixton to support the teaching of English as a foreign language (EFL) writing to students at a private university in southern Ecuador. For this purpose, 52 EFL students (male and female, aged 19–24 years old) who were enrolled in a writing course participated in the study for a period of five months. At the start, most of these students had an A1+ proficiency level, according to the Common European Framework of Reference for Languages (CEFR). The study employed an action research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In this way is noted a clear difference between the results of pre and post-test in written proficiency of the students above. These conditions are similar to previous studies, such as those conducted by Cabrera-Solano et al, (2021), who showed that the use of comic stips improved writing abilities, and indeed its use encourages motivation among the students. While Green (2015) demonstrated that comics, used by medical students improve writing skills and other positive competence like the effect of comics on their professional identity.…”
Section: Discussionsupporting
confidence: 90%
“…In this way is noted a clear difference between the results of pre and post-test in written proficiency of the students above. These conditions are similar to previous studies, such as those conducted by Cabrera-Solano et al, (2021), who showed that the use of comic stips improved writing abilities, and indeed its use encourages motivation among the students. While Green (2015) demonstrated that comics, used by medical students improve writing skills and other positive competence like the effect of comics on their professional identity.…”
Section: Discussionsupporting
confidence: 90%
“…As explained in the research results, 31 lesson ideas can be adopted to teach the reading narrative text. Compared to the number of previous studies on storyboards and pixtons which were only 5 studies (Cabrera-Solano et al, 2021;Foulsham et al, 2016;Hung, 2019;Naar, 2013;Purnomo, 2017). Thereby, the decision to conduct exploratory research sourced from these two websites turned out to be very precise.…”
Section: Levels Of Reading Comprehension Skills That Can Be Taught Us...mentioning
confidence: 89%
“…Some scientists as P. Cabrera-Solano, P. Gonzalez-Torres and C. Ochoa-Cueva [8], A. Maatuk, E. Elberkawi, S. Aljawarneh, H. Rashaideh, and H. Alharbiet [21]) and others [29], [24], [34], [18], [3], discuss different issues connected with University staff training to cope with on-line teaching successfully in lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…The second one describes lockdown experience. The teaching and learning experience in some countries as Ukraine [22], Turkey [3], Ecuador [8], Nigeria [17], [25], [36], Philippines [24], Colombia [34], India [11], Thailand [38], Vietnam [26] and the United Arab Emirates [13], Mexico [2] is shown. Nevertheless, there are some gaps need to be filled in order to solve the hottest teaching and learning problems.…”
mentioning
confidence: 99%